1998
DOI: 10.1021/es980336x
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of Indoor and Outdoor Air Pollutants in Rio de Janeiro, Brazil:  Implications to Indoor Air Quality in Bayside Offices

Abstract: An indoor air quality survey was conducted on selected floors in an office building in Rio de Janeiro, Brazil. The sampling sites comprised four offices located along the same vertical column of the building. Measurements were made on alternate days at the same time of day during working hours. Indoor and outdoor samples were collected for volatile organic compounds (VOC), formaldehyde, total suspended particles (TSP), nicotine, and ultraviolet respirable suspended particles (UV-RSP). Compared with formaldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 21 publications
3
45
2
4
Order By: Relevance
“…Os níveis de concentração de aldeídos em ambientes internos são, na maioria das vezes, maiores quando comparados com ambientes externos 1,69,75 . Por exemplo, os resultados obtidos por Brickus e colaboradores 75 , para um edifício de escritório no Rio de Janeiro, apresentaram uma razão média de concentração interna/externa de 2,6 para formaldeído e, 1,3 para acetaldeído.…”
Section: Ambientes Internosunclassified
See 1 more Smart Citation
“…Os níveis de concentração de aldeídos em ambientes internos são, na maioria das vezes, maiores quando comparados com ambientes externos 1,69,75 . Por exemplo, os resultados obtidos por Brickus e colaboradores 75 , para um edifício de escritório no Rio de Janeiro, apresentaram uma razão média de concentração interna/externa de 2,6 para formaldeído e, 1,3 para acetaldeído.…”
Section: Ambientes Internosunclassified
“…Por exemplo, os resultados obtidos por Brickus e colaboradores 75 , para um edifício de escritório no Rio de Janeiro, apresentaram uma razão média de concentração interna/externa de 2,6 para formaldeído e, 1,3 para acetaldeído. …”
Section: Ambientes Internosunclassified
“…Después de ajustar por el efecto de otras fuentes de formaldehído y de la ventilación, la asociación entre el humo del cigarro y la concentración de formaldehído se mantuvo. Estudios nacionales han reportado mayores concentraciones de formaldehído (105 µg/m 3 ) en locales sin fumadores (Pires y Carvalho 1999) y no han mostrado una correlación significativa entre la concentración de nicotina (derivada del humo del cigarro) y la concentración de formaldehído (Brickus et al 1998).…”
Section: Discussionunclassified
“…Emissions of a number of hydrocarbons and aldehydes and ketones have been observed during operation of dryprocess copiers; these include significant emissions of ethylbenzene, o-, m-, and p-xylenes, styrene, 2-ethyl-l-hexanol, acetone, nnonanal, and benzaldehyde (Leovic et al, 1996). Enhanced levels of acetaldehyde in an office building in Brazil were attributed to the oxidation of ethanol used as a cleaning agent (Brickus et al, 1998), although levels outdoors were also enhanced due to the use of ethanol as a fuel. Pyrocatechol has been measured in an occupational environment where meteorological charts are mapped on paper impregnated with this compound (Ekinja et al, 1995), and p-dichlorobenzene is observed when mothballs containing this compound are in use (e.g., Tichenor et al, 1990;Chang and Krebs, 1992).…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%